Athlete's heart 3D model design based on MRI data - Strelkov, S. V.; Avtyushenko, A. L.; Ivanov, V. M.; Solovyeva, A. A.; Vasilyev, N. V. (Theory and Practice of Physical Culture, 2017)
This article describes a simple and effective approach to design of a highly detailed model of heart. The three-dimensional model design method is based on the use of ventricular contours data obtained by MRI study. This method allows building a model of an athlete's heart with all internal structures, which allows to simplify the process of visualization and assessment of cardiac structures before and after the load and preventing a possible pathology.